The Influence Of Religiosity, Income, Zakat Literacy, And Socialization On The Interest In Paying Zakat: A Case Study Of Baitul Mal In Banda Aceh City - Dewi, Ratna; Nurlina, Eka; Umuri, Khairil (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2025)
This research aims to determine the influence of religiousness, income, zakat literacy, and socialization on people's interest in paying zakat at Baitul Mal, Banda Aceh City. The data used is primary data using a questionnaire technique which was distributed to 100 respondents, people who have KTPs in Banda Aceh. The number of variables studied was 5 (five), namely religiosity, income, zakat literacy, and socialization as independent variables and the variable interest in paying zakat as the dependent variable. The approach used in this research is a quantitative approach. The sampling method used is probability sampling with cluster random sampling technique. The method used is multiple linear regression analysis. Based on the results of this study, it was found that religiosity has a positive and significant effect on interest in paying zakat, income has a positive and significant effect on interest in paying zakat, zakat literacy has a positive and significant effect on interest in paying zakat, socialization has a positive and significant effect on interest in paying zakat, religiosity, income, zakat literacy and socialization simultaneously influence the intention to pay zakat.